Study of relation of type of fracture with amount of postoperative fluid therapy and duration of hospital stay after surgery - Sinha, Ritesh; Jaishi, Prakash Poudel; Neupane, Kiran Sandhya; Rajak, Ashik; Banjade, Prakash (Journal of Kathmandu Medical College, 2021)
Background: Post-earthquake in Nepal many patients were rescued by the Nepalese Army and transferred to Shree Birendra Hospital where they were managed and discharged postoperatively to the area with substandard care.Objectives: This study aimed to establish the relation of type of fracture with the amount of fluid infused/transfused and postoperative hospital stay during earthquake victim resuscitation and care in April 2015.Methods: Hospital based data registered during the period of 25th April 2015 to 15th May 2015 were collected for this analytical study design. Seventy-five orthopaedic cases were selected randomly and analysed with software Minitab 17.Results: Fifty-three patients had long bone fractures, out of which 32 were infused with low, 18 with moderate, and three with high amounts of fluids. Similarly, 15 patients with non-long bone fractures were infused with low and seven patients with moderate amounts of fluid. The Chi-square association between type of fracture and amount of postoperative fluid therapy is 1.418, DF = 2 with p = 0.49. Similarly, the Chi-square association between the type of fracture and duration of hospital stay is 5.423 with DF = 4 and p = 0.247.Conclusion: Long bone fractures are more debilitating but are not a cause for long hospital stay postoperatively. And there is no significant relationship between the type of fracture and the amount of postoperative fluid therapy. Hence during the time of disaster, patients can be cared for in the hospital ward for a certain time and shifted to other areas of sub-standard care. This in turn can accommodate large victims during such critical times.